The hierarchical status of mobility disability predicts future IADL disability: A longitudinal study on aging - Chen, Hui-Ya; Yeh, Chih-Jung; Wang, Ching-Yi; Lin, Hui-Shen; Lee, Meng-Chih (IntechOpen, 2012)
None